Emerging Parasitic Protists: The Case of Perkinsea - Itoïz, Sarah; Metz, Sebastian; Derelle, Evelyne; Reñé, Albert; Garcés, Esther; Bass, David; Soudant, Philippe; Chambouvet, Aurélie (Frontiers in Microbiology, 2022)
The last century has witnessed an increasing rate of new disease emergence across the world leading to permanent loss of biodiversity. Perkinsea is a micro-eukaryotic parasitic phylum dominated by generalist parasites with broad host ranges. Some perkinseans represent major ecological and economical threats because of their geographically invasive ability, high phenotypic plasticity and pathogenicity (leading to mortality events). In the marine environments, three families, the Parviluciferaceae, the Perkinsidae and the Xcellidae, infecting respectively dinoflagellates, molluscs and fish, are currently described. In contrast, only one group has been characterised in the freshwater environment: the Severe Perkinsea Infectious agent infecting frog tadpoles. High throughput sequencing methods, mainly based on 18S rRNA assays, have showed that Perkinsea is far more diverse than the previously four lineages described. In freshwater, some lineages could be parasites of green microalgae but a formal nature of the interaction needs to be explored. However, currently most of newly described aquatic clusters are only defined by their environmental sequences and are still not (yet) associated with any host. The unveiling of this microbial black box presents a multitude of research challenges to understand their ecological roles and ultimately to prevent their most negative impacts. This review summarises the biological and ecological traits of Perkinsea - their diversity, life cycle, host preferences, pathogenicity, and highlights their diversity and ubiquity in association with a wide range of hosts.